"...som dröjer kvar tack vare sin materiella tröghet i rummet" - den fysiska bokens värde, språk och anspråk i en digital samtid - Nielsen Jerneck,Hedvig Kristina Maria (2025)
The focus of this essay, titled ”…lingering, thanks to its material slowness in the room”, is the physical book and the question if this physical book has any value on the contemporary and digital book market. Another question is if in that case it would be possible to understand the physical book as an object of memories and of non-measurable, sensuous attention. The essay is based on the theory of such a value, a theory of the paratext and an extending theory of materiality and non-measurability. The extended theoretical discussion is also an important part of the methodological process, inspired by a phenomenological reasoning. Through an understanding of the contemporary book market as digital and through an understanding of the human being as part of her relationship to machines and technology, being at the same time a reader in spe, an open and sensitive reader, I’ll try to give a background of the analysis as to the physical book and its value in connection to relations, interspace and memorable materiality. The analysis is in three parts and discusses the physical book through articles, academic works and government reports, through essays and through an experimental investigation of six different physical books in different genres. Through the analysis, an understanding of the physical book appears as a connection or a relationship between (the reading) subject and the experiences given by the physical book as to attended interspaces, memories, sensuousness and an enduring slowness.
Keywords: bokmarknad; bransch i förändring; fysisk bok; digitalisering; värde; paratext; omätbarhet; människa; ofärdig; relationell; mellanrum; sinnlighet; uppmärksamhet; minne